Problems in management of medication overuse headache in transgender and gender non-conforming populations - Martinez, Cameron I.; Liktor-Busa, Erika; Largent-Milnes, Tally M. (Frontiers in Neurology, 2024)
Primary headache disorders, such as migraine, account for a significant portion of disability rates worldwide, yet patients still struggle to receive the adequate medical and emotional support necessary to improve health outcomes. Insufficient pain management through either impractical pharmaceutical treatments or absent emotional support networks can worsen physical and mental health outcomes since comorbidities commonly associated with headache include hypertension, diabetes, depression, and anxiety. A lack of awareness on headache pathology and its observable severity can lead to pain-related prejudice that destroys beneficial aspects of patient self-advocacy and self-efficacy, thus potentially discouraging the use of healthcare services in favor of maladaptive coping skills. Acute treatments for primary headache disorders include non-steroidal anti-inflammatory drugs (i.e., aspirin, ibuprofen), triptans (i.e., sumatriptan), and opioids; however, continuous use of these pain-relieving agents can generate a secondary headache known as medication overuse headache (MOH). Recent work highlighting the overlap of morphological and functional brain changes in MOH and substance use disorder (SUD) suggests that insufficient pain management encourages analgesic misuse. The LGBTQ+ community—specifically transgender and gender non-conforming persons—struggles with high rates of mental illness and substance abuse. Since gender-affirming sex hormone therapy influences migraine progression, transgender and gender non-conforming (trans*) patients on hormone therapy have a higher risk for worsening migraine symptoms. However, trans* patients are less likely to have access to appropriate pain management techniques, thus preventing positive health outcomes for this vulnerable population.